2000
DOI: 10.1038/labinvest.3780047
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Inducible Nitric Oxide Synthase to Mast Cells During Ischemia/Reperfusion Injury of Skeletal Muscle

Abstract: SUMMARY:Nitric oxide contributes to tissue necrosis after ischemia-reperfusion (IR). A biochemical and immunohistochemical study was made of the amounts and localization of both Ca ϩϩ -independent nitric oxide synthase (NOS) II and Ca ϩϩ -dependent (NOS I and NOS III) in rat skeletal muscle after ischemia and 0.5, 2, 8, 16, and 24 hours reperfusion. NOS II was not detectable in control muscle or during ischemia, was first detected after 2 hours reperfusion, increased further by 8 hours, and remained elevated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 35 publications
2
58
1
1
Order By: Relevance
“…Unlike our rat studies where even the most markedly degranulation mast cells could be detected with toluidine blue, 6 few such profiles were detected in the mouse. The rapid increase in toluidine blue positive mast cell density between 1 and 2 h of reperfusion was unexpected.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Unlike our rat studies where even the most markedly degranulation mast cells could be detected with toluidine blue, 6 few such profiles were detected in the mouse. The rapid increase in toluidine blue positive mast cell density between 1 and 2 h of reperfusion was unexpected.…”
Section: Discussioncontrasting
confidence: 44%
“…3,4 Our studies in rats demonstrated that the NO involved in IR injury was derived from NO synthase II (NOS II) and the use of NOS II inhibitors greatly improved survival of gastrocnemius skeletal muscle subjected to IR. 3 In ongoing IR studies it was revealed that NOS II protein was almost exclusively localized in mast cells, 5,6 and that the number of markedly degranulated mast cells increased within hours of reperfusion. Recent studies by Gilchrist et al, 7 confirm the presence of NOS II protein and mRNA in rat peritoneal mast cells.…”
mentioning
confidence: 99%
“…Neuronal NOS as a source of NO may assume greater importance in situations of endothelial dysfunction since inhibitors of neuronal NOS did not affect dilation of coronary arterioles to ACh in wild-type mice but decreased it in endothelial NOS –/– mice [43]. It is unlikely, however, that dilation to ACh could be due to NO from iNOS induced by the presence of cytokines because, although there is no current information about the effect of muscle activity on iNOS expression or function, chronic stimulation does not alter numbers of inflammatory macrophages [44]or mast cells [45], both potential sources of iNOS [46]. …”
Section: Discussionmentioning
confidence: 99%
“…[7,15] Various in vivo studies have shown that NO biosynthesis and its action are closely related to the pathogenesis of renal I/R injury. In addition, it has been shown that selective or non-selective iNOS inhibitors prevent I/R injury in skeletal muscle, myocardial infarction, brain, liver, and kidney tissues, [13,[16][17][18][19][20][21] and that iNOS-knockout mice show reduced I/R injury in the kidney. [20] Melatonin is mainly secreted from pineal gland and a variety of non-pineal tissues and organs, including the kidney.…”
Section: Introductionmentioning
confidence: 99%